Integrated quality assessment of sediments from harbour areas in Santos-São Vicente Estuarine System, Southern Brazil - Buruaem, Lucas Moreira [UNESP]; de Castro, Ítalo Braga; Hortellani, Marcos Antonio; Taniguchi, Satie; Fillmann, Gilberto; Sasaki, Silvio Tarou; Varella Petti, MÔnica Angélica; Sarkis, Jorge Eduardo de Souza; Bícego, Márcia Caruso; Maranho, Luciane Alves [UNESP]; Davanso, Marcela Bergo [UNESP]; Nonato, Edmundo Ferraz; et al. (Elsevier, 2013)
Santos-São Vicente Estuarine System is a highly populated coastal zone in Brazil and where it is located the major port of Latin America. Historically, port activities, industrial and domestic effluents discharges have constituted the main sources of contaminants to estuarine system. This study aimed to assess the recent status of sediment quality from 5 zones of Port of Santos by applying a lines-of-evidence approach through integrating results of: (1) acute toxicity of whole sediment and chronic toxicity of liquid phases; (2) grain size, organic matter, organic carbon, nitrogen, phosphorus, trace metals, polycyclic aromatic hydrocarbons, linear alkylbenzenes and butyltins; (3) benthic community descriptors. Results revealed a gradient of increasing contamination for metals and organic compounds, alongside with their geochemical carriers. Sediment liquid phases were more toxic compared to whole sediment. Low number of species and individuals indicated the impoverishment of benthic community. The use of site-specific sediment quality guidelines was more appropriate to predict sediment toxicity. The integration of results through Sediment Quality Triad approach and principal component analysis allowed observing the effects of natural stressors and dredging on sediment quality and benthic distribution. Even with recent governmental efforts to control, pollution is still relevant in Port of Santos and a threat to local ecosystems. © 2013 Elsevier Ltd.
Keywords: Dredged material; Integrated assessment; Lines-of-evidence approach; Marine pollution; Sediment quality triad; benthos; coastal zone; dredging; grain size; marine pollution; organic carbon; organic matter; port; principal component analysis; sediment analysis; toxicity; Brazil; Latin America; Santos; Sao Paulo [Brazil]; Sao Vicente [Sao Paulo]